The Impact of Concussion, Sport, and Time in Season on Saliva Telomere Length in Healthy Athletes - Machan, Matthew; Tabor, Jason B.; Wang, Meng; Sutter, Bonnie; Wiley, J. Preston; Mychasiuk, Richelle; Debert, Chantel T. (Frontiers in Sports and Active Living, 2022)
To date, sport-related concussion diagnosis and management is primarily based on subjective clinical tests in the absence of validated biomarkers. A major obstacle to clinical validation and application is a lack of studies exploring potential biomarkers in non-injured populations. This cross-sectional study examined the associations between saliva telomere length (TL) and multiple confounding variables in a healthy university athlete population. One hundred eighty-three (108 male and 75 female) uninjured varsity athletes were recruited to the study and provided saliva samples at either pre- or mid-season, for TL analysis. Multiple linear regression was used to determine the associations between saliva TL and history of concussion, sport contact type, time in season (pre vs. mid-season collection), age, and sex. Results showed no significant associations between TL and history of concussion, age, or sport contact type. However, TL from samples collected mid-season were longer than those collected pre-season [β = 231.4, 95% CI (61.9, 401.0), p = 0.008], and males had longer TL than females [β = 284.8, 95% CI (111.5, 458.2), p = 0.001] when adjusting for all other variables in the model. These findings population suggest that multiple variables may influence TL. Future studies should consider these confounders when evaluating saliva TL as a plausible fluid biomarker for SRC.